2018
DOI: 10.1007/s10111-018-0468-0
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing complexities: the human limits of air traffic control

Abstract: Air traffic management is organized into filters in order to prevent tactical controllers from dealing with complex conflicting situations. In this article, we describe an experiment showing that a dynamic conflict display could improve human performance on complex conflict situations. Specifically, we designed a display tool that represents the conflicting portions of aircraft trajectories and the evolution of the conflict zone when the user adds a maneuver to an aircraft. The tool allows the user to dynamica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…We checked how a tool capable of dynamically showing parts of potentially conflicting trajectories could help controllers separate aircraft for different levels of complexity. Durand et al (2018) showed in previous research using the CAT tool that the initial two year training of trainee ATCOs in France had a low impact on their capacity to manage complex situations. When comparing a group of trainee ATCOs with a group of engineering students who had the same age and scientific background without the ATC training experience, we did not see any significant difference except on delay management.…”
Section: Atcos' Cognitive Processesmentioning
confidence: 96%
See 1 more Smart Citation
“…We checked how a tool capable of dynamically showing parts of potentially conflicting trajectories could help controllers separate aircraft for different levels of complexity. Durand et al (2018) showed in previous research using the CAT tool that the initial two year training of trainee ATCOs in France had a low impact on their capacity to manage complex situations. When comparing a group of trainee ATCOs with a group of engineering students who had the same age and scientific background without the ATC training experience, we did not see any significant difference except on delay management.…”
Section: Atcos' Cognitive Processesmentioning
confidence: 96%
“…The conflict detection calculation was detailed by Durand et al (2018). Each trajectory is divided in line segments on which the aircraft has a constant speed.…”
Section: Conflict Detection Calculationmentioning
confidence: 99%
“…With respect to emergence of complex traffic patterns, visualization of air traffic complexity has been so far limited to post-analysis of historic data such as density maps of spatial data collected over several hours (Delahaye et al, 2004;Andrienko et al, 2018) and visualizing conflicting parts of trajectories (Durand et al, 2018). In this thesis, however, I propose visualization concepts which show information about emerging complex patterns in near future and present possible complexity-reduction solutions in real-time.…”
Section: Visual Analytics Of Air Transportation Datamentioning
confidence: 99%
“…different components in the free trajectory space. It is suggested that any method requiring exploring every connected component is NP-difficult [37]. Moreover, the number of potential solutions in the solution space grows exponentially.…”
Section: Levels Of Trafficmentioning
confidence: 99%